Comparison of Parenting Stress and Locus of Control in Parents of Children with and without Specific Learning Disorder - Seyed Omid Sotoudeh Navroodi; Mojgan Sotuodeh Navroodi (Journal of Modern Psychology)
Objective: Families frequently experience a variety of wonderful occurrences and, at times, face difficult circumstances, such as the birth of a child with special needs. These conditions can profoundly affect the dynamics of a family. This research aimed to examine parental stress and locus of control between parents of children with certain learning disorder and those without.Methods: This study utilized a descriptive-comparative methodology. The statistics population comprised all primary school students in the city of Talesh during March to June 2024. The research sample consisted of 116 people (56 parents of children with specific learning disorder and 60 parents with children without specific learning disorder) who were selected through purposive sampling. The data were analyzed using the Parenting Stress Index (PSI) and the Internal-External Locus of Control (IPC) scale. Multivariate analysis of variance and independent t-tests were employed to analyze the data.Results: The findings revealed a notable disparity in parental stress and locus of control between parents of children with specific learning disorder and those without (P<0.05).Conclusion: The findings indicate that parents of children with learning disorder endure elevated stress levels and a heightened perception of loss of control, hence increasing their risk.